PEMBELAJARAN KOMUNIKASI LINGKUNGAN YANG BERTANGGUNG JAWAB PADA GENERASI Z - Lydia Irena; Michelle Augustine (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
Today’s global environmental challenges call for a fundamental shift in mindset and behavior toward more sustainable patterns of consumption and production. The Sustainable Development Goals (SDGs), particularly Goal 12, emphasize the importance of responsible consumption and production as the foundation of sustainable development. In this context, the younger generation—especially Generation Z—holds a strategic role as agents of change, particularly through their influence in digital spaces. This Community Service Program (Program Pengabdian kepada Masyarakat or PKM) is designed to equip Generation Z with the knowledge and skills necessary for responsible environmental communication, as part of efforts to achieve SDG 12. This program is grounded in environmental communication theory, which views communication as a vital tool in fostering awareness, critical attitudes, and collective action toward ecological issues. Through an educational approach combining seminars and workshops, participants are encouraged to understand current environmental challenges and to develop message strategies that promote behavioral change regarding consumption. Seminars serve as Platforms for delivering material and facilitating discussion, while workshops provide participatory spaces for developing media-based communication initiatives. This PKM represents an academic contribution to fostering sustainable environmental awareness among young people through a transformative communication approach, aligned with global sustainable development objectives. After the implementation of the interactive seminar and workshop, there was a significant increase in the understanding of the participants. Overall, the average increase in participants' insight rose from 3.6 to 4.6. These results reflect the effectiveness of interactive learning methods that are relevant to the characteristics of generation Z in improving environmental literacy communicatively Permasalahan lingkungan hidup global saat ini menuntut adanya perubahan pola pikir dan perilaku terhadap konsumsi dan produksi yang lebih berkelanjutan. Agenda Sustainable Development Goals (SDGs) khususnya tujuan ke-12 menekankan pentingnya pola konsumsi dan produksi yang bertanggung jawab sebagai fondasi pembangunan berkelanjutan. Dalam konteks ini, generasi muda—khususnya Generasi Z—memiliki peran strategis sebagai agen perubahan, terutama melalui pengaruh mereka di ruang digital. Program Pengabdian kepada Masyarakat (PKM) ini dirancang untuk membekali generasi Z dengan pemahaman dan keterampilan dalam komunikasi lingkungan yang bertanggung jawab sebagai bagian dari upaya mencapai SDG ke-12. Kegiatan ini mengacu pada teori komunikasi lingkungan yang memandang komunikasi sebagai instrumen penting dalam membangun kesadaran, sikap kritis, dan tindakan kolektif terhadap isu-isu ekologi. Melalui pendekatan edukatif berbasis seminar dan lokakarya, peserta diajak untuk mengenali tantangan lingkungan masa kini serta bagaimana membingkai pesan yang mampu mendorong perubahan perilaku konsumtif. Seminar digunakan sebagai wadah penyampaian materi dan diskusi, sedangkan lokakarya berfungsi sebagai ruang partisipatif untuk mengembangkan inisiatif komunikasi berbasis media. PKM ini merupakan bentuk kontribusi akademik dalam membentuk kesadaran lingkungan yang berkelanjutan di kalangan generasi muda melalui pendekatan komunikasi yang transformatif, sejalan dengan tujuan global pembangunan berkelanjutan. Setelah pelaksanaan seminar dan lokakarya interaktif terjadi peningkatan signifikan dalam pemahaman para peserta. Secara keseluruhan, rerata peningkatan wawasan peserta naik dari 3,6 menjadi 4,6. Hasil ini mencerminkan efektivitas metode pembelajaran yang interaktif dan relevan dengan karakteristik generasi Z dalam meningkatkan literasi lingkungan secara komunikatif.